US adult smokers' perceived relative risk on ENDS and its effects on their transitions between cigarettes and ENDS - Sooyong Kim; Saul Shiffman; Mark A. Sembower (BMC, 2022)
Abstract Background Perceived risk reduction motivates smokers to switch to electronic nicotine delivery systems (ENDS). This research examines US smokers' relative risk perceptions and their prospective association with various behavioral stages of switching to ENDS. Methods Data from the nationally representative, longitudinal Population Assessment of Tobacco and Health (PATH) Adult survey, Waves 1 (2014) through 5 (2019), were analyzed. We assessed the association between the perceived risk of ENDS relative to cigarettes ("less harmful" vs. "equally harmful" or "more harmful") and 1) adoption of ENDS (among never-ENDS-using smokers), 2) complete switching to ENDS (i.e., stopping smoking, among ever-ENDS-using smokers), and 3) avoiding reversion to smoking (among smokers who had switched to ENDS), at the next wave. Results The proportion of US smokers perceiving ENDS as less harmful than cigarettes continually decreased, reaching 17.4% in Wave 5 (2019). Current smokers with such belief were more likely to adopt ENDS (aOR 1.31; 95% CI 1.15-1.50) and switch completely to ENDS (aOR 2.24; 95% CI 1.89-2.65) in the subsequent wave. Among smokers who had switched within the past year, such beliefs predicted avoidance of resumption of smoking in the next wave (aOR 0.55; 95% CI 0.33-0.93). Conclusions Smokers' beliefs about the relative risk of ENDS compared to cigarettes had a strong and consistent association with transitions between smoking and ENDS use. Addressing the growing misperception about ENDS has the potential to contribute to public health by encouraging smokers' switching to ENDS.